2010
DOI: 10.1002/ijc.25024
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition with bortezomib suppresses growth and induces apoptosis in osteosarcoma

Abstract: Osteosarcomas are primary bone tumors of osteoblastic origin that mostly affect adolescent patients. These tumors are highly aggressive and metastatic. Previous reports indicate that gain of function of a key osteoblastic differentiation factor, Runx2, leads to growth inhibition in osteosarcoma. We have previously established that Runx2 transcriptionally regulates expression of a major proapoptotic factor, Bax. Runx2 is regulated via proteasomal degradation, and proteasome inhibition has a stimulatory effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Of specific interest is the gene RUNX2, which resides within the orthologous regions defined by HSA 6p21.1 and CFA 12q13. Several recent studies have focused on investigating the dysregulation of RUNX2 in human OS Sadikovic et al, 2009Sadikovic et al, , 2010San Martin et al, 2009;Shapovalov et al, 2010), and the comparability of our data suggests that RUNX2 merits further investigation in both species.…”
Section: Discussionmentioning
confidence: 46%
“…Of specific interest is the gene RUNX2, which resides within the orthologous regions defined by HSA 6p21.1 and CFA 12q13. Several recent studies have focused on investigating the dysregulation of RUNX2 in human OS Sadikovic et al, 2009Sadikovic et al, , 2010San Martin et al, 2009;Shapovalov et al, 2010), and the comparability of our data suggests that RUNX2 merits further investigation in both species.…”
Section: Discussionmentioning
confidence: 46%
“…The accumulated data have revealed that targeting UPS components such as proteasomes offers great promise as a novel therapeutic strategy for cancer [34,35]. When newly synthesized proteins in the ER do not present a correct folding, they are translocated to the cytosol where they are immediately subjected to proteasomal degradation [13].…”
Section: Discussionmentioning
confidence: 99%
“…These OS cell lines have been extensively characterized by our group, as evident from our previous studies (8,25,28). Importantly, the LM7 cell line is an invasive and metastatic subtype of the parental Saos2 cell line (29), and the 143B cell line is an invasive and metastatic subtype of the parental HOS cell line (30).…”
Section: Presence Of the Warburg Effect In Lm7 And 143b Osteogenicmentioning
confidence: 92%
“…Electron Microscopy-Cultured cells or tissue pieces of xenografted OS tumors produced as described in our previous study (25) were fixed in 2.5% glutaraldehyde in 0.1 M sodium cacodylate buffer, post-fixed in 1.0% OsO 4 , dehydrated with ethanol, and transitioned into propylene oxide for infiltration and embedding into EPON/Araldite epoxy resin. Thin sections were cut onto grids, stained with uranyl acetate and lead citrate, examined with a Hitachi H-7650 transmission electron microscope, and digitally photographed.…”
Section: Methodsmentioning
confidence: 99%